HUBUNGAN MOTIVASI DIRI TERHADAP KEPATUHAN MELAKSANAKAN DIET PADA PENDERITA HIPERTENSI - Sari, Delima; Safri, Safri; Utami, Gamya Tri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Hypertension is one of non-communicable diseases. Hypertension was categorized by the value of systolic blood pressure more than 130 mmHg and diastolic blood pressure more than 80 mmHg. These hypertension precautions are committed by self-motived in controlling blood pressure, and execute a hypertension diet. The aim of this research was to know the relationship between self-motivated and compliance with carrying out a diet in hypertension‘s patients used descriptive correlative design and cross sectional approach involving 73 respondents selected by the inclusion criteria by using purposive sampling technique by using chi-square test. This biivariate analysis showed that from 39 respondent (73,6%) with high motivation obeyed hypertenti’s  diet. Bivariate analysis showed that p value is 0,016 (p value <0.05, which concluded that there was correlation between self-motivated and the obedience did the hypertension’s diet on hypertension’s victim. Based on study findings, it is known that hypertension’s patients should taking care the hypertension’s diet to control the blood pressure.  Keyword : Hypertension, hypertension diet, self-motivated